The comparison of the influence of transdermal and oral hormonal replacement therapy on general feeling of women after hystero-adnexectomy - Samulak, Dariusz; Sajdak, Stefan (Menopause Review/Przegląd Menopauzalny, 2010)
Introduction: Patients who have undergone hysterectomy with adnexectomy have the same symptoms as women during the perimenopausal period. In order to alleviate these symptoms and prevent distant effects of oestrogen deficiency, the use of continuous oestrogen therapy is recommended. Aim of the study: The aim of this work was to compare the effects of oral and transdermal hormonal replacement therapy in patients after hystero-adnexectomy. Material and methods: The study covered a group of 80 patients, who were divided into two subgroups. The first subgroup was administered a transdermal preparation with estradiol and the second one – an oral preparation. The control group consisted of 60 patients, who did not consent to the hormonal therapy (HT). The degree of intensity of climacteric symptoms was evaluated in each group at the time of the operation, 3 months and 6 months after the operation. Severity of symptoms was rated using Kuppermann scale. Results: There were no differences in the incidence of climacteric symptoms in particular degrees between the two groups before the surgery. After 3 months, a decrease in the incidence of severe and moderate climacteric symptoms in patients receiving HT was observed. After 6 months, only 8% of patients with transdermal HT and 6% of patients with oral HT reported climacteric symptoms, in the control group patients reported a further increase in complaints. Conclusions: Women applying oestrogen therapy after surgery are less vulnerable to incidence of menopausal symptoms. The expected results are achieved earlier after oral HT, while the effects are far more satisfactory when applying transdermal HT